2012
DOI: 10.1155/2012/185167
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Spinal Astrocytic JAK2-STAT3 Pathway Activation Correlates with the Analgesic Effects of Triptolide in the Rat Neuropathic Pain Model

Abstract: Neuropathic pain (NP) is an intractable clinical problem without satisfactory treatments. However, certain natural products have been revealed as effective therapeutic agents for the management of pain states. In this study, we used the spinal nerve ligation (SNL) pain model to investigate the antinociceptive effect of triptolide (T10), a major active component of the traditional Chinese herb Tripterygium wilfordii Hook F. Intrathecal T10 inhibited the mechanical nociceptive response induced by SNL without int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 52 publications
6
47
0
Order By: Relevance
“…36,37 In the current study, activated pSTAT3 was localized in astrocytes ( fig. 36,37 In the current study, activated pSTAT3 was localized in astrocytes ( fig.…”
Section: Pain Medicinesupporting
confidence: 56%
“…36,37 In the current study, activated pSTAT3 was localized in astrocytes ( fig. 36,37 In the current study, activated pSTAT3 was localized in astrocytes ( fig.…”
Section: Pain Medicinesupporting
confidence: 56%
“…Similarly, Tang et al . reported the antinociceptive effects of triptolide were related with activation of spinal astrocytic JAK‐STAT3 Pathway. Our previous study showed that inhibition of the spinal RANTES expression contributes to BCP in rats .…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies demonstrated the involvement of astrocytic Jak-Stat3 pathway in the regulation of neuropathic pain [13], [14]. In rats undergoing spinal nerve ligation injury, Stat3 acts as a critical transducer that converts resting glia to reactive astrocytes for the maintenance of tactile allodynia [13].…”
Section: Discussionmentioning
confidence: 99%